2021
DOI: 10.1021/jacs.1c00108
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Control of Supramolecular Polymerization and Gelation of Metal–Organic Polyhedra

Abstract: In coordination-based supramolecular materials such as metallogels, simultaneous temporal and spatial control of their assembly remains challenging. Here, we demonstrate that the combination of light with acids as stimuli allows for the spatiotemporal control over the architectures, mechanical properties, and shape of porous soft materials based on metalorganic polyhedra (MOPs). First, we show that the formation of a colloidal gel network from a preformed kinetically trapped MOP solution can be triggered upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 68 publications
1
33
0
Order By: Relevance
“…More recently, Furukawa et al also showed an alternative way to trigger the gelation of C 12 -RhMOP(bix) 12 via acid-triggered detachment of bix. [40] They found that addition of stoichiometric amounts of trifluoroacetic acid (TFA) to a DMF solution of C 12 -RhMOP(bix) 12 triggered gelation at room temperature. By replacing TFA with the photoacid 8-hydroxypyren-1,3,6trisulfonic acid (pyranine), they were able to synthesize porous gels upon light irradiation at room temperature, thereby enabling photo-patterning of the gel.…”
Section: Assembly Of Mops Through N-based Ditopic Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Furukawa et al also showed an alternative way to trigger the gelation of C 12 -RhMOP(bix) 12 via acid-triggered detachment of bix. [40] They found that addition of stoichiometric amounts of trifluoroacetic acid (TFA) to a DMF solution of C 12 -RhMOP(bix) 12 triggered gelation at room temperature. By replacing TFA with the photoacid 8-hydroxypyren-1,3,6trisulfonic acid (pyranine), they were able to synthesize porous gels upon light irradiation at room temperature, thereby enabling photo-patterning of the gel.…”
Section: Assembly Of Mops Through N-based Ditopic Ligandsmentioning
confidence: 99%
“…The use of MOPs as building blocks for porous networks presents several advantages such as the possibility to confer extended materials with permanent porosity regardless of the final degree of order of these materials, since both the functionalization and integrity of the cage—particularly for those with strong metal–ligand coordination bonds—are thoroughly maintained during the polymerization step. [ 40 ] This in turn paves the way for the controlled embedding of porosity into soft matter such as gels or self‐assembled monolayers. Alternatively, the possibility to precisely locate reactive sites on the polyhedral surface of MOPs with accurate knowledge of their number, location, and orientation enables the use of MOPs as pre‐synthesized supermolecular building blocks that can be assembled into highly connected crystalline nets via reticular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This area has advanced as one of the most important scientific problems for solving complex networking pattern in nature, such as -connectivity in living cells or neuronal network or creating next-generation materials with perceptual stability. [3][4][5][6][7][8][9] Agonistic or antagonistic relationship between different constituents are the key factor or switches between the up-and downregulation of the whole dynamic processes. [10][11][12][13][14] In many cases, reaction-diffusion related to oscillatory system has been used to create non-equilibrium assembly and thereby surface pattern.…”
Section: Introductionmentioning
confidence: 99%
“…When used as secondary building blocks, MOPs can be assembled with additional linkers into colloidal particles or colloidal gel networks, in which the porosity of MOPs can be retained. [32][33][34][35][36][37][38][39] However, all of these systems have been assembled only from a single MOP and cross-linker component. Therefore, the integration of more than two distinct components during the self-assembly process remains a major challenge due to the lack of methodology.…”
Section: Introductionmentioning
confidence: 99%